2020
DOI: 10.1055/s-0040-1701622
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Cerebellar Endometriosis

Abstract: Endometriosis is a disorder in women which is characterized by extrauterine manifestations. We describe a case of cerebellar endometriosis in a 39-year-old woman who underwent posterior fossa decompression multiple times without establishing a correct diagnosis. Her neurologic status progressively worsened due to chronic hydrocephalus and brainstem compression by cysts. Late in the clinical course, histology from the cyst wall was taken that revealed endometriosis with clear cells and positive immunohistology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…All the cases collected, including our case, concerned women who showed an onset of neurological or psychiatric symptoms during the childbearing age (20–44 years). All cases found in the literature review were described by specialists in the neurological or gynecological field, including four clinical cases described by neurologists [ 40 , 41 , 42 , 45 ], two provided by gynecologists [ 44 , 46 ], and one by a gynecologist together with a neurologist [ 43 ]. While neurological symptoms dominated the clinical picture in most cases, psychiatric disorders were never reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the cases collected, including our case, concerned women who showed an onset of neurological or psychiatric symptoms during the childbearing age (20–44 years). All cases found in the literature review were described by specialists in the neurological or gynecological field, including four clinical cases described by neurologists [ 40 , 41 , 42 , 45 ], two provided by gynecologists [ 44 , 46 ], and one by a gynecologist together with a neurologist [ 43 ]. While neurological symptoms dominated the clinical picture in most cases, psychiatric disorders were never reported.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral endometriosis has been identified with certainty in four woman via the histological analysis of the lesions after surgical removal [ 40 , 41 , 42 , 45 ]. In two of these cases, brain MRI findings that were suggestive of cerebral endometriosis had been previously discovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMS can be traditionally divided into three types, i.e., peritoneal, ovarian EMS and deep invasive EMS. Rare EMS cases of distal organs, such as thoracic EMS and cerebellar EMS, have been reported in case reports (Meggyesy et al, 2020;Chen and Li, 2021). However, the pathophysiology of EMS is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated prevalence of endometriosis in the female population is about 1-10% depending on sampling and diagnostic methods [2,3]. Extragenital endometriosis usually occurs in the pelvic organs, but like cancer, it can spread seeding into the brain [4], lungs [5], or other sites. Circulating endometrial cells capable of disseminating were found in about 80% of patients with endometriosis [6].…”
Section: Introductionmentioning
confidence: 99%